2011
DOI: 10.1016/j.jclinepi.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Hospital discharge data can be used for monitoring procedures and intensive care related to severe maternal morbidity

Abstract: Intensive care and procedures seem reliably reported in the hospital administrative database, which, therefore, can be used to monitor them. Using these data for monitoring diagnoses will require a greater investment by clinicians in the accuracy of their reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 39 publications
5
99
0
1
Order By: Relevance
“…Furthermore, several studies have demonstrated the validity and quality of such data extracted from the French nationwide hospital database. 22,26,27 For postoperative sepsis in particular, we used the patient safety indicator (PSI), which is an internationally recognized metric for this type of data. The codes for cholecystectomy are similarly robust, as they are extracted from the French common classification of medical procedures (CCAM), which is analogous to the Current Procedural Terminology (CPT) system used in American health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several studies have demonstrated the validity and quality of such data extracted from the French nationwide hospital database. 22,26,27 For postoperative sepsis in particular, we used the patient safety indicator (PSI), which is an internationally recognized metric for this type of data. The codes for cholecystectomy are similarly robust, as they are extracted from the French common classification of medical procedures (CCAM), which is analogous to the Current Procedural Terminology (CPT) system used in American health care.…”
Section: Discussionmentioning
confidence: 99%
“…The French nationwide hospital database in acute care includes information with acceptable validity about all inpatient stays that have occurred in every French public and private hospital. 22 Standard discharge abstracts for each of these hospitalizations contain compulsory demographic information; primary and secondary diagnoses using the International Classification of Diseases, 10th revision (ICD-10 codes); emergency status; intensive care unit (ICU) admission; as well as procedural codes associated with the care provided (Appendix 1).…”
Section: Data and Populationmentioning
confidence: 99%
“…Diagnoses identified are coded according to the International Classification of Diseases, Tenth Revision. The reliability of PMSI data has already been assessed, 17,18 and PMSI has previously been used to study patients with stroke, myocardial infarction, and AF. [19][20][21] The study population comprised adults with a diagnosis of acute ischemic stroke (I63 and its subsections using International Classification of Diseases, Tenth Revision codes) coded in the principal diagnosis (ie, the health problem that justified admission to hospital), the related diagnosis (ie, potential chronic disease or health state during hospital stay), or the significantly associated diagnosis (ie, comorbidity or associated complication) who were hospitalized from January 1 to December 31, 2009.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…The reliability and validity of PMSI data have already been assessed. 18,19 Since 2004, each hospital's budget has depended on the medical activity described in this specific program, which compiles discharge abstracts related to all admissions in the 1546 French healthcare facilities, whether public or private. Information in these abstracts covers both medical and administrative data, including social security number, date of birth, and sex.…”
Section: Selection Of Patientsmentioning
confidence: 99%